Probiotics in hepatology - Lata, Jan; Jurankova, Jana; Kopacova, Marcela; Vitek, Petr (World journal of gastroenterology, 2011)
The paper provides a basic review of intestinal microflora and its importance in liver diseases. The intestinal microflora has many important functions, above all to maintain the microbial barrier against established as well as potential pathogens. Furthermore, it influences the motility and perfusion of the intestinal wall, stimulates the intestinal immune system and therefore also the so-called common mucosal immune system, reducing bacterial translocation and producing vitamins. Immune homeostasis at mucosal level results from a controlled response to intestinal luminal antigens. In liver cirrhosis, there are many changes in its function, mostly an increase in bacterial overgrowth and translocation. In this review, probiotics and their indications in hepatology are generally discussed. According to recent knowledge, these preparations are indicated in clinical practice only for cases of hepatic encephalopathy. Probiotics are able to decrease the permeability of the intestinal wall, and decrease bacterial translocation and endotoxemia in animal models as well as in clinical studies, which is extremely important in the prevention of complications of liver cirrhosis and infection after liver transplantation. Probiotics could limit oxidative and inflammatory liver damage and, in some situations, improve the histological state, and thus non-alcoholic steatohepatitis could be considered as another possible indication.
Keywords: Probiotics; nemoci jater; lidé; gastroenterologie; Gastroenterology; Non-alcoholic steatohepatitis; gastrointestinální trakt; Liver cirrhosis; Humans; Liver Diseases; Liver encephalopathy; Intestinal microflora; Gastrointestinal Tract; probiotika